Precipitation Observations in Rolwaling Valley, eastern Nepal Himalayas, in summer 2019 - Hatsuki Fujinami; Koji Fujita; Yota Sato; Hironari Kanamori; Rakesh Kayastha; Rijan B Kayastha (PANGAEA, 2022)
To better understand summer precipitation, including extreme events at higher elevations in the Himalayas and its variability, we installed rain gauges in Singati, Gongar, Simigaun, Dongang, Beding, and Na along the Rolwaling valley of the eastern Nepal Himalayas, leading to the Trambau/Trakading glaciers in May 2019. The dataset contains hourly records from the rain gauge stations, which measured precipitation by tipping bucket. The total amount of precipitation during the preceding hour was considered as the hourly precipitation. The data covers from June to September 2019. The data provided here represents a cleaned dataset extracted from the original data logger files.